THE DEVELOPMENT OF A JĀTAKA STORY-BASED COMIC BOOK FOR ELEMENTARY BUDDHIST SUNDAY SCHOOL STUDENTS - Ayuvadhana, Nandiya; Widiyono, Widiyono; Parsiyono, Parsiyono (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2022)
The purpose of this study is to explain the manufacturing process and determine the feasibility level of jātaka comic books. The method used in this research is Research and Development using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The data collection techniques used include observation, interviews, questionnaires, and documentation. The data credibility is assessed by transferability, dependability, and confirmability. The data analysis techniques used for qualitative data are reduction, presentation, conclusion and verification. Meanwhile, quantitative data are analyzed using descriptive percentage theory. The result of the research is the process of making jātaka comic books based on the ADDIE development model. Based on the results of the product feasibility assessment from experts, jātaka comic book get a feasibility percentage of 89.95% from material experts and 75% from media experts. The test subjects involved were 2 BSS teachers and 7 BSS students at the Elementary School level at BSS Dhamma Mettā. The responses of BSS students during product trials seemed interested, enthusiastic, and able to understand the contents of the jātaka comic book. The BSS teacher said that jātaka comic books were easy to use and suitable as teaching materials. Based on the results of the percentage assessment and responses from the test subjects, it can be said that the jātaka comic book is suitable to be used as teaching material for BSS at the elementary school level at BSS Dhamma Mettā.